Efektivitas Proyek Perubahan Diklat Kepemimpinan Tingkat IV di Pemerintah Provinsi DKI Jakarta - Djumadiono, Djumadiono (Komunitas Manajemen Kompetitif, 2021)
One of the strategies to improve the performance of government agencies is innovation. Innovation is expected to affect the optimization of existing resources in order to achieve performance targets. The objective of this study was to determine the effectiveness of educational innovation and leadership training conducted by the DKI Jakarta provincial government through the Leadership Training Change Project. The results showed that there were several obstacles experienced by the participants in making post-training change project efforts such as lack of stakeholder support (20.68%), changes in nomenclature (2.95%), due to mutations (37.55%), lack of funding (32.91%), and lack of leadership support (5.91%). Change management is used as a basis for innovative value transformation so as to provide excellent service. Service orientation and justification of openness values ​​will make the change project more flexible in presenting new internal organizational values.